A Qualitative Study Exploring Menstruation Experiences and Practices among Adolescent Girls Living in the Nakivale Refugee Settlement, Uganda - Kemigisha, Elizabeth; Rai, Masna; Mlahagwa, Wendo; Nyakato, Viola N.; Ivanova, Olena (International Journal of Environmental Research and Public Health, 2020)
Girls in low- and lower-middle income countries face challenges in menstrual health management (MHM), which impact their health and schooling. This might be exacerbated by refugee conditions. This study aimed at describing menstruation practices and experiences of adolescent girls in Nakivale refugee settlement in Southwestern Uganda. (2) Methods: We conducted a qualitative study from March to May 2018 and we intentionally selected participants to broadly represent di erent age groups and countries of origin. We conducted 28 semistructured interviews and two focus group discussions. Data were transcribed and translated into English. Analysis included data familiarization, manual coding, generation and refining of themes. (3) Results: Main findings included: (a) challenging social context with negative experiences during migration, family separation and scarcity of resources for livelihood within the settlement; (b) unfavorable menstruation experiences, including unpreparedness for menarche and lack of knowledge, limitations in activity and leisure, pain, school absenteeism and psychosocial e ects; (c) menstrual practices, including use of unsuitable alternatives for MHM and poor health-seeking behavior. (4) Conclusions: Amultipronged approach toMHMmanagement is crucial, including comprehensive sexual education, enhancement of parent–adolescent communication, health sector partnership and support from NGOs to meet the tailored needs of adolescent girls
Keywords: refugee; adolescent; menstruation; sexual and reproductive health